A Simple Whole-Blood Test for Detecting Antibodies to Human Immunodeficiency Virus - Schramm, Willfried (American Society for Microbiology, 1998)
We developed an immunochromatographic whole-blood test (WBT) which detects antibodies to human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) from fingerstick blood. The sensitivity and specificity of the WBT were 99.41% (1,018 confirmed positive patients) and 99.89% (941 uninfected patients), respectively (enzyme immunoassay [EIA] on serum or plasma as a reference). WBT performance was comparable to those of licensed EIAs and Western blotting, using 18 HIV-2 sera, 23 HIV-1 seroconversion panels, and a low-titer performance panel (in lieu of whole blood).